PERILAKU MEMBERI MAKAN UNTUK MENINGKATKAN TUMBUH KEMBANG ANAK - Husaini, Yayah K. (GIZI INDONESIA, 2006)
FEEDING BEHAVIOUR FOR BETTER GROWTH AND DEVELOPMENTThe widespread malnutrition in children especially among those under two years of age is closely linkage not only to poverty but also to inappropriate child caring practices particularly feeding behavior and infection. Complementary foods given into an infant’s diet in addition to breast milk after the child above 6 months old either commercially or specially prepared at home are needed to meet the nutrient requirements. The Pengalengan study shows that children with better nutritional status because of local food supplements in early infancy perform better cognition in later life. Therefore, to empower women who are the main caregiver with knowledge and skill is necessary to optimal nutritional benefits for their children.Key wood: Feeding behaviour, growth, development